Chemopreventive effects of a low-side-effect antibiotic drug, erythromycin, on mouse intestinal tumors - Hamoya, Takahiro (J Clin Biochem Nutr, 2017)
It is important to establish effective methods for preventing colorectal cancer because the number of colorectal cancer deaths is increasing. Erythromycin one of the macrolide antibiotics, has been shown to exert pleiotropic effects, such as anti-inflammatory and anti-oxidative effects, on mammalian cells. In the present study, we aimed to evaluate the preventive effects of erythromycin on intestinal carcinogenesis. We first confirmed that erythromycin suppresses the transcriptional activity of nuclear factor-κB and activator protein-1 and the expression of its downstream targets, interleukin-6 and cyclooxygenase-2 in human colon cancer cells. Next, we fed 5-week-old male Apc mutant Min mice with diets containing 500 ppm erythromycin for 15 weeks. Erythromycin treatment significantly reduced the number of proximal intestinal polyps to 70.9% of the untreated control value. Moreover, erythromycin reduced the levels of interleukin-6 and cyclooxygenase-2 mRNA expression in intestinal polyps. Although the levels of hepatic NADPH oxidase mRNA were decreased, erythromycin treatment did not affect the levels of oxidative stress markers, reactive carbonyl species, in the liver of Min mice. Our results suggest that erythromycin suppresses intestinal polyp development in Min mice, in part by attenuating local inflammation, and indicate that erythromycin is useful as a chemopreventive agent.